ÓZBEK HÁM QARAQALPAQ TIL BILIMINDE FRAZEOLOGIYALÍQ SISTEMASÍNÍŃ IZERTLENIW TARIYXÍ - Arzimbetova, S.A. (SCIENCE and SOCIETY, 2024)
The article deals with the history of the study of phraseological units in Uzbek and Karakalpak linguistics. It also provides information about the study of phraseological units divided into periods and the current comparative study process.
Keywords: phraseological units; phrases; semantic features of phraseological units; classification of phraseology; types of phraseological units